2020
DOI: 10.1016/j.ejvs.2020.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Assessment Predicts Aneurysm Related Events in Patients with Abdominal Aortic Aneurysm

Abstract: Apologies -this was a typo that is now corrected. The correct presentation of the study is 'MA 3 RS' and we do not believe this will cause problems with the reader interpreting the superscript as a reference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Our work builds upon previous efforts by our group and collaborators regarding the biomechanical modeling and characterization of AAA in-vivo behavior [ 10 16 ], as well as several previous studies indicating that biomechanical indices are more accurate predictors for AAA rupture risk than the clinically established maximum diameter criterion [ 17 24 ]. In contrast to the approaches in [ 17 20 , 22 , 24 ], however, we advocate a probabilistic treatment to account for uncertain vessel wall properties. Our work thus goes along the lines of [ 21 ], but with the key difference that it includes the stiffness parameters of the AAA vessel wall as statistical quantities, uses patient-specific vessel wall properties and accounts for statistical correlations among these properties.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our work builds upon previous efforts by our group and collaborators regarding the biomechanical modeling and characterization of AAA in-vivo behavior [ 10 16 ], as well as several previous studies indicating that biomechanical indices are more accurate predictors for AAA rupture risk than the clinically established maximum diameter criterion [ 17 24 ]. In contrast to the approaches in [ 17 20 , 22 , 24 ], however, we advocate a probabilistic treatment to account for uncertain vessel wall properties. Our work thus goes along the lines of [ 21 ], but with the key difference that it includes the stiffness parameters of the AAA vessel wall as statistical quantities, uses patient-specific vessel wall properties and accounts for statistical correlations among these properties.…”
Section: Introductionmentioning
confidence: 75%
“…In addition with regression models [ 13 , 26 , 27 ] for the prediction of the individual wall strength, this enabled the definition of biomechanics-based indices [ 19 , 20 , 22 , 28 ], such as the rupture potential index (RPI) relating the von Mises stress to the wall strength. Furthermore, it could be shown [ 19 , 20 , 24 ] that these indices can be better rupture risk indicators than the maximum diameter criterion.…”
Section: Methodsmentioning
confidence: 99%
“…Examples of suggested alternative predictors include characteristics of the intraluminal thrombus (ILT) 5 , 19 22 , tracer imaging of AAA vessel wall metabolism, calcification processes and inflammation 23 25 as well as circulating markers of extracellular matrix degradation, inflammation, coagulation and microRNAs 26 . Further, finite element analysis (FEA) has in several retrospective case-control studies been reported to predict rupture 27 33 but also to predict growth or future surgery 34 , 35 . As of yet, none of these alternative markers have been included into clinical management algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…was used by Polzer and Gasser [26]. A prospective study [6] collected 13 ruptured cases in about 2~3 years of follow up period. In this study, ATAA risks (PRR) were retrospectively reconstructed by FE simulation using pre-operative images and tissue testing data of 41 patients who underwent elective surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the clinical surgery criterion is primarily based on the aortic size and classifies an ascending thoracic aortic aneurysm (ATAA) as high risk if the (maximum) diameter is larger than 5.5cm [2,3], which may not accurately reflect a patient's risk [4,5]: some aneurysms at smaller diameters (e.g., < 4cm) can and do rupture [4]. As ATAA rupture and dissection are essentially mechanical events, patient-specific biomechanical assessment, such as structural finite element analysis (FEA), can provide a more accurate assessment of ATAA rupture/dissection risk [6,7]. Using 3D patientspecific aorta geometry and physiological blood pressure, aortic wall stresses can be computed using FEA.…”
Section: Introductionmentioning
confidence: 99%